Eco-friendly Bi(Ni2/5Ti2/5Fe1/5)O3 nanoceramics: Synthesis, dielectric and impedance studies. Issue 15 (1st August 2021) - Kumar, Nitin; Shukla, Alok; Kumar, Nripesh; Agarwal, Ravi; Choudhary, R.N.P.
Abstract: This investigation involves the synthesis and study of dielectric, structural and impedance properties of polycrystalline Bi(Ni2/5 Ti2/5 Fe1/5 )O3 (symbolized as BNTF) nano-ceramic. The BNTF polycrystalline sample was fabricated through the use of a conventional solid-state reaction route. X-ray structural examination reveals that the parent compound (i.e., BiFeO3 ) crystallizes in the rhombohedral structure (space group-R3c) while that the BNTF compound crystallizes in orthorhombic symmetry. The substitution of NiTiO3 into BiFeO3 enhances various properties and reduces electrical leakage current. The average crystallite size is calculated to be 29 nm. The room temperature textures and surface morphologies of the specimen were verified by field-emission scanning electron microscope, and show uniform grains distribution on sample surfaces. Dielectric parameters (constant and tangent-loss) and impedance spectroscopy parameters of NiTiO3 modified BiFeO3 compound were investigated over a wide temperature range (25–500 °C) at different frequency (25 kHz-500 kHz), which offers several interesting features of BNTF material suitable for further device applications.